Pembentukan Kelompok Pendukung Asi Untuk Percepatan Capaian Asi Eksklusif Dan Pencegahan Stunting Di Kelurahan Fobaharu Kecamatan Tidore Utara - Matjino, Sitti Hubaya; Usman, Supriyanti R (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
There is still a stigma and stereotype that is closely attached to most Indonesian people, namely that breastfeeding is only a matter for women or mothers. In essence, women have the nature to breastfeed, but men have an important role in providing support for mothers to continue breastfeeding so that exclusive breastfeeding is achieved and continued with breast milk and complementary foods (MP ASI) until the child is 2 years old. Data collection and interviews with breastfeeding mothers by students of the Midwifery Department while conducting Field Work Practices (PKL) in Fobaharu Village, Rumbali bunga Health Center Work Area, North Tidore District, obtained data that out of eight babies, four babies under the age of six months had been given complementary foods (MP ASI), the low understanding of mothers and the Fobaharu community about exclusive breastfeeding, the low support of husbands, families and the community for breastfeeding mothers. The purpose of this activity is to form a breastfeeding support group and to increase the knowledge, skills, awareness and understanding of all components of society about the importance of Exclusive Breastfeeding in preventing Stunting. By providing socialization, training, and direct practice to the Breastfeeding Support Group. The results showed an increase in participant knowledge with a sufficient category of 67%, and good 33% pretest and after training (posttest) it became good 89%, the skills of participants were very skilled in performing good and correct breastfeeding techniques as many as 9 people, the skills of participants in performing oxytocin massage according to the observation sheet as many as 8 people, and the skills of participants in performing good and correct counseling techniques as many as 9 people, the skills of participants in performing oxytocin massage according to the observation sheet as many as 8 people, and the skills of participants in performing counseling techniques correctly as many as 5 people.